Effect of supplementation of sea buckthorn leaf meal on egg production performances of coloured breeder birds during winter season (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted to study the effect of sea buckthorn leaf meal (SBTLM)  supplementation on hen house and hen day egg production in ninety coloured Chabro adult breeder hens  and 18 viable cocks in 1:5 sex ratio were randomly distributed into three dietary treatment groups: Control,  standard basal breeder diet (BIS, 2007); basal+0.5% and basal+1.0% SBTLM. The average egg production  during 9th week onward till the entire period of experimentation were significantly higher (p
Keywords: Breeder; Chabro and SBTLM; Coloured chicken